Factors That Influence Public Non-Compliance In Paying Motor Vehicle Tax - Putri, Devi Lestari Pramita; Alfisalam, Naily (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
This research lies in the domain of local taxation, focusing on public noncompliance in paying motor vehicle taxes. The purpose of this study is to analyze the influence of tax sanctions, tax socialization, and the E-Samsat system on taxpayer compliance. The study was conducted on 100 motor vehicle taxpayers in Pamekasan Regency using a quantitative approach and multiple linear regression analysis. The results show that both partially and simultaneously, tax sanctions, tax socialization, and E-Samsat have a significant effect on taxpayer compliance. These findings confirm that strong legal enforcement, ongoing tax education, and accessible digital services such as E-Samsat can increase public compliance. This study provides significant contributions to strengthening local government efforts in optimizing tax revenue through strategies that enhance taxpayer compliance. The conclusion of this study emphasizes the importance of combining regulatory, educational, and technological approaches in building a sustainable local taxation system.